Association of Habitual Physical Activity Measured by an Accelerometer with High-Density Lipoprotein Cholesterol Levels in Maintenance Hemodialysis Patients - Ryota Matsuzawa; Atsuhiko Matsunaga; Toshiki Kutsuna; Akira Ishii; Yoshifumi Abe; Kei Yoneki; Manae Harada; Mio Ishibashi; Yasuo Takeuchi; Atsushi Yoshida; Naonobu Takahira (The Scientific World Journal)
After confirming the relationship between high-density lipoprotein cholesterol (HDL-C) levels and mortality in hemodialysis patients for study 1, we investigated the effect of physical activity on their HDL-C levels for study 2. In study 1, 266 hemodialysis patients were monitored prospectively for five years, and Cox proportional hazard regression confirmed the contribution of HDL-C to mortality. In study 2, 116 patients were recruited after excluding those with severe comorbidities or requiring assistance from another person to walk. Baseline characteristics, such as demographic factors, physical constitution, primary kidney disease, comorbid conditions, smoking habits, drug use, and laboratory parameters, were collected from patient hospital records. An accelerometer measured physical activity as the number of steps per day over five consecutive days, and multiple regression evaluated the association between physical activity and HDL-C levels. Seventy-seven patients died during the follow-up period. In study 1, we confirmed that HDL-C level was a significant predictor of mortality (P=0.03). After adjusting for patient characteristics in study 2, physical activity was independently associated with HDL-C levels (adjusted R2=0.255; P=0.005). In conclusion, physical inactivity was strongly associated with decreased HDL-C levels in hemodialysis patients.